Are patients with cancer at higher risk of COVID-19-related death? A systematic review and critical appraisal of the early evidence. (September 2022) - Freeman, Victoria; Hughes, Suzanne; Carle, Chelsea; Campbell, Denise; Egger, Sam; Hui, Harriet; Yap, Sarsha; Deandrea, Silvia; Caruana, Michael; Onyeka, Tonia C.; IJzerman, Maarten J.; Ginsburg, Ophira; et al.
Abstract: Background: Early reports suggested that COVID-19 patients with cancer were at higher risk of COVID-19-related death. We conducted a systematic review with risk of bias assessment and synthesis of the early evidence on the risk of COVID-19-related death for COVID-19 patients with and without cancer. Methods and findings : We searched Medline/Embase/BioRxiv/MedRxiv/SSRN databases to 1 July 2020. We included cohort or case-control studies published in English that reported on the risk of dying after developing COVID-19 for people with a pre-existing diagnosis of any cancer, lung cancer, or haematological cancers. We assessed risk of bias using tools adapted from the Newcastle-Ottawa Scale. We used the generic inverse-variance random-effects method for meta-analysis. Pooled odds ratios (ORs) and hazard ratios (HRs) were calculated separately. Of 96 included studies, 54 had sufficient non-overlapping data to be included in meta-analyses (>500, 000 people with COVID-19, >8000 with cancer; 52 studies of any cancer, three of lung and six of haematological cancers). All studies had high risk of bias. Accounting for at least age consistently led to lower estimated ORs and HRs for COVID-19-related death in cancer patients (e.g. any cancer versus no cancer; six studies, unadjusted OR=3.30, 95%CI:2.59–4.20, adjusted OR=1.37, 95%CI:1.16–1.61). Adjusted effect estimates were not reported for people with lung or haematological cancers. Of 18 studies that adjusted for at least age, 17 reported positive associations between pre-existing cancer diagnosis and COVID-19-related death (e.g. any cancer versus no cancer; nine studies, adjusted OR=1.66, 95%CI:1.33–2.08; five studies, adjusted HR=1.19, 95%CI:1.02–1.38). Conclusions: The initial evidence (published to 1 July 2020) on COVID-19-related death in people with cancer is characterised by multiple sources of bias and substantial overlap between data included in different studies. Pooled analyses of non-overlapping early data with adjustment for at least age indicated a significantly increased risk of COVID-19-related death for those with a pre-existing cancer diagnosis. Highlights: Early studies on risk of COVID-19-related death and cancer have high risk of bias. There was substantial overlap between data included in different early studies. Meta-analyses suggest higher risk of COVID-19-related death for people with cancer. Stratified estimates by cancer type, time since diagnosis, and treatment are needed.